2010
DOI: 10.1136/jramc-156-01-07
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administration of Exercise and Dietary Supplements in Deployed British Military Personnel During Operation TELIC 13

Abstract: This is the first study to investigate the use of exogenous nutritional supplements within the British Military and has identified their widespread use during operational deployment. The use of anabolic steroids is particularly worrying, given both their illegality and their well-recognised and deleterious health effects. There is a need for greater awareness and education regarding potential benefits and dangers of supplement use in order to maximise any potential benefits and minimise clinical risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 25 publications
3
56
1
1
Order By: Relevance
“…Another study found greater DS use by United States Marines who were deployed to Afghanistan (Cassler et al 2013). The prevalence of overall DS use we observed among deployed personnel was much higher than the 35%-40% levels reported in the recent studies of British soldiers deployed in Afghanistan or Iraq, but this may reflect differences in the questionnaires used in each study (Boos et al 2010(Boos et al , 2011 or general differences between British and American DS use. In the United States compared with the United Kingdom a much wider variety of DSs are available.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Another study found greater DS use by United States Marines who were deployed to Afghanistan (Cassler et al 2013). The prevalence of overall DS use we observed among deployed personnel was much higher than the 35%-40% levels reported in the recent studies of British soldiers deployed in Afghanistan or Iraq, but this may reflect differences in the questionnaires used in each study (Boos et al 2010(Boos et al , 2011 or general differences between British and American DS use. In the United States compared with the United Kingdom a much wider variety of DSs are available.…”
Section: Discussioncontrasting
confidence: 51%
“…Interestingly, our findings of DS use among deployed personnel are remarkably similar to DS use by United States Marines deployed to the same region of conflict (Cassler et al 2013). Previous reports of DS use for deployed soldiers (Boos et al 2010(Boos et al , 2011Cassler et al 2013;Jacobson et al 2012) did not directly compare deployed and garrison personnel using the same survey instrument as was done in the current investigation. Therefore, this report is the first we are aware of that definitively demonstrates that patterns of DS use change during deployment.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations